Liquid-liquid equilibria of UCON + (sodium or potassium) phosphate salt aqueous two-phase systems at 23 °C - Silvério, Sara C. (2010)
Six phase diagrams for UCON−phosphate salt aqueous two-phase systems (ATPSs), at 23 °C, are presented. The ATPSs were obtained combining UCON (a random copolymer of 50 % ethylene oxide and 50 % propylene oxide) and a phosphate salt (KH2PO4, K2HPO4, potassium phosphate buffer pH = 7, NaH2PO4, Na2HPO4, and sodium phosphate buffer pH = 7). Among the salts used, Na2HPO4 proved to be the most effective in ATPS formation, providing the greatest heterogeneous region in the phase diagram. The previous established relation between the anion valence and the concentration needed to form a biphasic system was confirmed: higher valence requires lower concentration. Na+ salts require, in all cases, lower concentration to form ATPSs than the corresponding K+ salts. The size of the heterogeneous region in the phase diagrams increases with an increase of the pH value of the salt used in ATPS preparation.